2021
DOI: 10.1055/a-1287-7482
|View full text |Cite
|
Sign up to set email alerts
|

Traction-assisted endoscopic full-thickness resection followed by O-ring and over-the-scope clip closure in the stomach: an animal experimental study

Abstract: Background and study aims Exposed endoscopic full-thickness resection (EFTR) enables the operator to obtain a sufficient surgical margin. However, insufflation leakage and secure endoscopic full-thickness closure (EFTC) remain problematic. This study aimed to evaluate the safety and feasibility of a new exposed EFTR. Patients and methods Exposed EFTR was performed for 2-cm virtual lesions in different locations of the upper stomach in four dogs. EFTR mainly involved half-circumferential EFTR of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 16 publications
0
18
0
1
Order By: Relevance
“…Similarly, this case series demonstrated that gastric full-thickness defects were successfully closed with OTSCs in all 14 cases. As shown in our video, the OTSC closure system enables us to achieve inverted seromuscular apposition [12,13]. A previous study indicated that inverted serosal apposition provides a more durable and reliable repair than everted mucosal apposition [14].…”
Section: Discussionmentioning
confidence: 66%
“…Similarly, this case series demonstrated that gastric full-thickness defects were successfully closed with OTSCs in all 14 cases. As shown in our video, the OTSC closure system enables us to achieve inverted seromuscular apposition [12,13]. A previous study indicated that inverted serosal apposition provides a more durable and reliable repair than everted mucosal apposition [14].…”
Section: Discussionmentioning
confidence: 66%
“…In comparison with previously reported methods, modified LACC was easily available without special devices, because hand suturing and purse-string require a two-channel endoscope, and expensive devices are required for OTSC and OverStitch. However, median closure time for modified LACC (43.5 minutes) was not shorter than that of other reported methods for similar defect size in porcine or human studies: hand suturing, median 25 to 49.5 minutes 9 10 ; O-ring and OTSC, median 35.5 minutes 12 ; and pure-string suture, mean 14.6 minutes 8 . Further developments are needed to reduce procedure time.…”
Section: Discussionmentioning
confidence: 66%
“…a Multiple small incisions (basically eight incisions) just outside the defect were made circumferentially. minutes) was not shorter than that of other reported methods for similar defect size in porcine or human studies: hand suturing, median 25 to 49.5 minutes [9,10]; O-ring and OTSC, median 35.5 minutes [12]; and pure-string suture, mean 14.6 minutes [8]. Further developments are needed to reduce procedure time.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73…”
Section: Current Status Of Eftr: Various Applications With Outcomesunclassified